Faith-Driven Innovation in Practice: Investigating MBKM within Islamic Higher Education in Indonesia - Jufriadi, Jufriadi; Wahibah, Wahibah (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2025)
In an era marked by rapid educational transformation, the Merdeka Belajar-Kampus Merdeka (MBKM) initiative emerges as a critical reform in Indonesian higher education, designed to bridge academic learning with real-world competencies. However, limited research has explored how this policy aligns with the foundational philosophies and pedagogical values of Islamic Higher Education Institutions (IHEIs), which prioritize ethical, spiritual, and intellectual development rooted in maqasid al-shariah. This study examines the implementation of the MBKM program in Islamic Higher Education Institutions (IHEIs) in Indonesia. Using a qualitative case study approach, data were collected through semi-structured interviews and institutional document analysis to explore alignment with Islamic educational philosophy. Thematic coding revealed three major findings: first, MBKM activities such as internships and community service resonate with Islamic principles of service (khidmah) and societal benefit (maslahah); second, institutional resistance and lack of resources hinder integration; and third, MBKM fosters opportunities for curriculum innovation that preserve Islamic identity while enhancing employability. The study contributes to the discourse on educational reform by offering a culturally responsive model of policy adaptation in religious institutions. It also provides actionable recommendations for aligning national policy with faith-based education. These findings have broader implications for advancing inclusive and value-driven higher education that respects religious traditions while embracing modernity.